Evaluation of combined use of Oxyma and HATU in aggregating peptide sequences. (31st January 2017) - Caporale, Andrea; Doti, Nunzianna; Sandomenico, Annamaria; Ruvo, Menotti
Abstract : Polypeptides are finding increasing applications as therapeutics because of their specificity that often translates into excellent safety, tolerability, and efficacy profiles in humans. New synthetic methodologies for their preparation are thereby continuously sought to reduce the costs associated to chain assembly and purification. Although solid‐phase peptide synthesis has become one of the most advanced synthetic procedures at both laboratory and industrial scale, the process is often complicated by aggregation phenomena originating from the combined occurrence of intermolecular and intramolecular hydrogen bonding, hydrophobic interactions, or other effects. Altogether, these effects cause accumulation of many side products and synthetic mixtures extremely hard to separate and purify, strongly affecting the costs of the final material. In the attempt to optimize the coupling steps of some well‐known aggregating or otherwise difficult to obtain peptides, we have comparatively investigated the use of Oxyma/DIC and HATU/Sym‐collidine as second coupling reagents in double coupling settings for the preparation of some model peptides. Comparative analytical data obtained on the unpurified products with the two different protocols clearly show that the use of Oxyma/DIC largely improves the content of the target molecules in the final crude materials, making the synthesis more convenient and cost‐effective. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : We have evaluated the use of Oxyma/DIC as a coupling agent in solid‐phase peptide synthesis. The use of Oxyma/DIC combined with HATU/Sym‐collidine in a double coupling setting largely improves the yields in aggregation‐prone peptide segments. The use of Oxyma/DIC increases the content of the target molecules in the final crude materials, making the synthesis more convenient and cost‐effective.